Modelo Prolab: Ksaflex, construcción sostenible de viviendas modulares mediante el uso de paneles de madera plástica plegables - Guerrero Chenique, Sofía Lorena (2024)
The housing deficit in Peru affects approximately 1.9 million families in socioeconomic levels D and E, who live in precarious conditions without access to adequate basic services. This problem is aggravated by variable incomes and labor informality, which limit access to mortgage loans and the possibility of acquiring decent housing. The proposed solution is the construction of affordable housing using wood-plastic panels, an innovative and sustainable material made from recycled plastic waste. This approach not only reduces environmental impact, but also lowers construction costs, making housing more affordable for low-income families. To validate the feasibility of the solution, financial simulations were conducted under pessimistic, optimistic and conservative scenarios. The results indicated that the project is economically viable, with a positive Net Present Value (NPV) of S/. 2’002,276.53. In addition, a sustainable growth in the demand for low-cost housing and a significant reduction in production costs due to the use of recycled materials were projected. The social impact is expected to improve the quality of life of families in socioeconomic levels D and E, providing them with safe and adequate housing that promotes their well-being and development. In addition to promoting circular economy practices. In summary, the proposal for housing with wood plastic panels offers an integral and sustainable solution to the housing deficit in Peru, especially for the NSE D and E, effectively addressing social, environmental and economic problems.